Sequential Cyk-4 binding to ECT2 and FIP3 regulates cleavage furrow ingression and abscission during cytokinesis - Simon, Glenn C (Nature Publishing Group, 2008)
Cytokinesis is a highly regulated and dynamic event that involves the reorganization of the cytoskeleton and membrane compartments. Recently, FIP3 has been implicated in targeting of recycling endosomes to the mid-body of dividing cells and is found required for abscission. Here, we demonstrate that the centralspindlin component Cyk-4 is a FIP3-binding protein. Furthermore, we show that FIP3 binds to Cyk-4 at late telophase and that centralspindlin may be required for FIP3 recruitment to the mid-body. We have mapped the FIP3-binding region on Cyk-4 and show that it overlaps with the ECT2-binding domain. Finally, we demonstrate that FIP3 and ECT2 form mutually exclusive complexes with Cyk-4 and that dissociation of ECT2 from the mid-body at late telophase may be required for the recruitment of FIP3 and recycling endosomes to the cleavage furrow. Thus, we propose that centralspindlin complex not only regulates acto-myosin ring contraction but also endocytic vesicle transport to the cleavage furrow and it does so through sequential interactions with ECT2 and FIP3.